Intravital multiphoton photoconversion with a cell membrane dye. Issue 2 (19th July 2016) - Turcotte, Raphaël; Wu, Juwell W.; Lin, Charles P.
Abstract : Photoconversion, an irreversible shift in a fluorophore emission spectrum after light exposure, is a powerful tool for marking cellular and subcellular compartments and tracking their dynamics in vivo . This paper reports on the photoconversion properties of Di‐8‐ANEPPS, a commercially available membrane dye. When illuminated with near‐infrared femtosecond laser pulses, Di‐8‐ANEPPS undergoes multiphoton photoconversion as indicated by the supralinear dependence of the conversion rate ρ pc on the incident power ( ρ pc ∝ I e x c 2.27 ), and by the ability to photoconvert a thin optical section in a three‐dimensional matrix. The characteristic emission spectrum changed from red to blue, and ratiometric analysis on single cells in vitro revealed a 65‐fold increase in the blue to red wavelength ratio after photoconversion. The spectral shift is preserved in vivo for hours, making Di‐8‐ANEPPS a useful dye for intravital cell marking and tracking applications. Abstract : The color of the moon can change during a lunar eclipse so can certain fluorescent dyes when light is shone on them. The changes in fluorescence emission spectrum, termed photoconversion, can be highly controlled, thus making this process a useful tool tostudy biological process in vivo at the cellular and subcellular levels. This Letter describes intravital multiphoton photoconversion of Di‐8‐ANEPPS, a membrane dye, in murine bone marrow.